Syntactic Models of Identifying Utterances: An Attempt at Generalisation (on the Material of the Russian Language) - Дымарский, Михаил Я. (Slavic Languages Today: Categories, Structures and Processes, 2021)
This article summarises the results of a study of syntactic models of identifying utterances in the Russian language. The study stems from the idea that systems of structural and structural-semantic sentence models in Slavic languages developed in the second half of the twentieth century provide a reasonable understanding of syntactic systems of these languages, but they do not bring us closer to understanding the process of generating an utterance. This process can be explained by the study of syntactic models of speech, which are approached as models derived from basic language ones. They have a close connection with the non-linguistic situation and the communicative situation, and have a number of fixed parameters. Each speech model is a set of utterance models which are based on it. They are even more closely associated with typical situations of reality and communication and have a larger number of fixed parameters. These are, in particular, the models of identifying utterances of two classes: (i) Это / N1 Vf (Eto ‘this’ / N1 Vf) and (ii) Так вот + [вопр. предл.] (Tak vot ‘So this is’ + [interrogative clause]). The logic of (i) and (ii) consists in identifying a present situation or its component with an image of this situation (component of a situation) in the active sphere of the speaker’s consciousness. Class (i) is more often used to identify the situation as a whole (Что это за шум за окном? – Это самолет летит / What’s this noise outside? – It’s a plane flying, lit. This a plane is flying); therefore, (i) can be called bi-situational utterances. Class (ii) is more often used to identify a component that involves specificational knowledge (O. Yokoyama), without which the speaker could not build a holistic view of the situation (Так вот где вы прячетесь, сорванцы! / So this is where you hide, tomboys!). This study considers differences between classes (i) and (ii). The pragmatic difference is that (ii) is impossible in a situation where the speaker has the specificational knowledge prior to uttering the sentence, while (i) not only does not exclude such situations, but also tends to be used namely in them. The semantic difference is that in (i) the identifiable situation or its component gets a meaningful name, while in (ii) the identifiable component is denoted by a pronoun that refers simultaneously to this component and to its image in the speaker’s mind, cf. Deixis am Phantasma (K. Bühler). On this basis, class (i) can be called nominative-identifying, and class (ii) – deictic-identifying. Finally, the difference between (i) and (ii) lies also in the diverse relationship of these speech models to the basic syntactic models of the language system: in particular, utterances of class (i) cannot use some models of subjectless sentences.